The effectiveness of sharp end and rounded end bristle toothbrush - Paulus Januar; Anastasia Susetyo; Ratih Widyastuti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: Numerous designs of manual toothbrush are available in the market with the claims of superiority in plaque removal. It often makes the public confuse which is the best design. The sharp end bristle toothbrush is a modification that commercially available in the market. Purpose: The objective of the study was to compare the effectiveness in plaque removal of the sharp end bristle toothbrush and the rounded end bristle toothbrush. Methods: This clinical trial was a double blind crossover design. The subjects were 65 dental students, divided into two groups for comparing the 2 types of toothbrush. On the 1st day, the allocated toothbrushes were distributedto each group according to their designation, and the subjects were instructed to use the toothbrushes according their normal daily practices. On the 1st, 7th, and 14th day, the subjects were scored using the patient hygiene performance index (PHP index) and the gingival index. Based on cross over design, the same procedure was repeated during the 2 week second test periods using different type of toothbrush respectively. Results: The mean scores of the 2 groups showed no significant difference on the beginning the study. Though minor differences were observed in the effectiveness of toothbrush, but the comparison of the two types of toothbrush showed no statistically significant differences on 7th and 14th day. Conclusion: There were no significant differences between sharp end and rounded end bristle toot brusher. There is no manual toothbrush superiorly designed than the others single superior design of manual toothbrush.Latar belakang: Berbagai jenis desain sikat gigi saat ini terdapat di pasaran, dengan masing-masing menyatakan keunggulannya dalam membersihkan plak. Penelitian ini dilakukan terhadap dua jenis sikat gigi manual yaitu sikat gigi dengan ujung bulu sikat runcing dan ujung bulus sikat bulat. Tujuan: Penelitian ini dilakukan untuk membandingkan efektivitas membersihkan plak antara 2 jenis sikat gigi. Metode: Penelitian ini merupakan percobaan klinis dengan desain penyilangan (crossover) secara tertutup ganda (double blind). Subyek penelitian 65 mahasiswa dibagi 2 kelompok. Pada hari pertama, sikat gigi dibagikan pada masing-masing kelompok yang telah ditentukan jenis sikat giginya, dan diinstruksikan untuk menggunakannya sesuai kebiasaan mereka. Pada hari ke 1, 7, dan 14 dilakukan pengukuran indeks PHP dan indeks gingiva. Berdasarkan desain penyilangan, proses yang sama diulangi pada masing-masing kelompok dengan menggunakan jenis sikat gigi yang berbeda. Hasil: Pada awal penelitian tidak terdapat perbedaan skor pada ke 2 kelompok. Meski terdapat sedikit perbedaan, namun tidak terdapat perbedaan yang bermakna dalam efektivitas kedua jenis sikat gigi setelah penggunaan selama 7 dan 14 hari. Kesimpulan: Tidak ada perbedaan yang bermakna antara sikat gigi jenis ujung bulu sikat bulat dan ujung bulu sikat runcing. Tidak terdapat satupun jenis sikat gigi yang paling baik.